UPAYA AUSTRALIA MELALUI PROGRAM EASTERN INDONESIA NATIONAL ROAD IMPROVEMENT PROJECT (EINRIP) DALAM MEMBANTU MENGURANGI KEMISKINAN DI GIANYAR - Ardyana Putra, I Putu Asta; Rainy Priadarsini, Ni Wayan; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT Poverty is a problem that occurred in the Eastern Indonesia. Poverty that occurred caused by the limited access of road network. Indonesian government had been tried to develop the road network in the Eastern Indonesia, and one of Indonesian Government policy on developing the road network was through development cooperation with Australian Government by EINRIP programme. One of the EINRIP programme location was located in Gianyar Regency. Gianyar Regency was selected as one of the EINRIP programme location was intended to open the road access as a main access for villages in the east coast of Gianyar Regency, all at once as a main access for connecting the Western and Eastern Indonesia. It is interesting to examine how the Australian efforts through EINRIP programme on reducing poverty in the Gianyar Regency. Keywords: Access, Poverty, Australia, EINRIP